THE EDUCATIVE VALUES OF HAJJ: IMPLEMENTING THE EDUCATIVE VALUES OF HAJJ INTO THE SCHOOL CURRICULUM - Abdullah Latuapo (Erudio Journal of Educational Innovation, 2021)
Hajj has become part of the rituals of previous religions long before Islam in various nations, including Arabs. Hajj, however, must not be seen simply as a ritual—it indeed has contextual meaning. In other words, one must understand the essence of hajj for the sole purpose of perfect obedience to Allah SWT (kaaffah). This study aimed to analyze the importance of hajj to school-age children’s education. We tried to contextually interpret the ritual (hajj) to develop the learning curriculum of the Islamic Religious Education (Pendidikan Agama Islam - PAI) from elementary, secondary, and senior high school levels. Our findings confirmed four educative values of hajj powerfully relevant to the Islamic Religious Education: relationality between Allah SWT as the Creator and human beings as the creation, relationality among human beings, relationality between human beings and other beings, and relationality of human beings with themselves. Those relationality values are then integrated into each scope of the curriculum of the Islamic Religious Education at the elementary, secondary, and senior high school levels.